1998
DOI: 10.1097/00005344-199800001-00013
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and Endothelin-Converting Enzyme-1 Gene Regulation by Shear Stress and Flow-Induced Pressure

Abstract: Hemodynamic forces have been shown to modulate the expression of endothelin (ET-1) and endothelin-converting enzyme (ECE-1) in endothelial cells. We have subjected E.A. hy 926 cells in culture to steady fluid shear stress with and without flow-induced pressure. The effect of combining these two mechanical forces on the expression of genes in the ET system was studied and the changes were compared to the mRNA levels in static culture. Analysis of total RNA by Northern blot analysis and RNAse protection showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Recently, the importance of the hemody- namic forces on ECs has become evident, both at the level of cell morphology as well as at the level of gene expression (1, 4). Moreover, it has been demonstrated that different hemodynamic conditions reproduced in in vitro experiments induce opposite effect on ECs, particularly in the context of endothelial nitric-oxide synthase, vascular cell adhesion molecule-1, and growth factor gene expression (5,6,8,26). All of these data suggest that unidirectional flow, typical of plaque-free areas, exerts a "protective" effect on endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the importance of the hemody- namic forces on ECs has become evident, both at the level of cell morphology as well as at the level of gene expression (1, 4). Moreover, it has been demonstrated that different hemodynamic conditions reproduced in in vitro experiments induce opposite effect on ECs, particularly in the context of endothelial nitric-oxide synthase, vascular cell adhesion molecule-1, and growth factor gene expression (5,6,8,26). All of these data suggest that unidirectional flow, typical of plaque-free areas, exerts a "protective" effect on endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…Although increasing in vitro data suggest that changes in mechanical forces alter ET-1 signaling, few data are available on the regulation of ET receptor signaling. 23,24 Therefore, the potential mechanisms for the current receptor changes are unknown and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…First, Hishikawa et al reported that pure pressure up to 160 mm Hg without flow increases ET-1 release from umbilical vein endothelial cells and that this effect is mediated by phospholipase C and protein kinase C pathways (24). Second, Harrison et al found no effect of flow-induced pressure (80 -160 mm Hg) on ET-1 and ECE-1 in E. A. hy 926 cells (25). In our study, we attempted to mimic the in vivo situation in pulmonary circulation as closely as possible, which included the selection of pulmonary cells as well as the application of flow-related pressures and shear stresses that reflect in vivo data (4,13,14).…”
Section: Discussionmentioning
confidence: 99%